Северяне посульского пограничья Древней Руси ІХ—ХІ вв. - Сухобоков, О.В. (Археологія і давня історія України, 2010)
В статье представлен обзор социо-культурных
процессов «огосударствления» населения северянского
племенного союза Днепровского Левобережья Русью в IX—XI ст. Стаття подає огляд соціо-культурних процесів
«одержавлення» населення сіверянського племінного союзу Дніпровського Лівобережжя Руссю у IX—XI ст. On the basis of archaeological data the paper describes
prosesses of cultural and social changes in life
of population of the Slavonic Severjane tribal union
during it’s integration in state and cultural system of
the Old Rus of the IX—XI centuries A.D.